Bribery: What Do Australian Managers Know and What Do They Do? - Segon , Michael; Booth , Chris (Journal of Law and Governance, 2011)
The recent conviction and gaoling of former Rio Tinto executive Stern Hu and as well as a further 18 Australian citizens facing charges in relation to "fraud and other economic crimes raises a number of questions regarding ethical business practice. A key issue that should be considered is whether Australian businesses are as ethical and transparent as the current high ranking in the Transparency International corruption index tends to suggest. This paper reviews literature pertaining to the normalisation of corrupt practices and the extent to which organisational members and managers are aware of and take action to report such practices. The paper will also present the findings of a survey of over 100 practicing managers that identifies whether they are aware of unethical practices and what they would do if they were to offer or receive an offer to engage in unethical practices. The survey focuses on a major corrupt practice, namely bribery. It also considers the reaction of managers to the request or order of a senior manager to engage in unethical practices inclusive of bribery. Conclusions will then be drawn regarding the extent of normalisation of corruption in Australian organisations.